Realization of a three-dimensional photonic higher-order topological insulator - Ziyao Wang; Yan Meng; Bei Yan; Dong Zhao; Linyun Yang; Jingming Chen; Minqi Cheng; Tao Xiao; Perry Ping Shum; Gui-Geng Liu; Yihao Yang; Hongsheng Chen; et al. (Nature Communications)
Abstract The discovery of photonic higher-order topological insulators (HOTIs) has expanded our understanding of band topology, offering robust lower-dimensional boundary states for photonic devices. However, realizing three-dimensional (3D) photonic HOTIs remains challenging due to the vectorial and leaky nature of electromagnetic waves. Here, we present the experimental realization of a 3D Wannier-type photonic HOTI using a tight-binding-like metal-cage photonic crystal, whose band structures align with a 3D tight-binding model via confined Mie resonances. Microwave near-field measurements reveal coexisting topological surface, hinge, and corner states in a single 3D photonic HOTI, consistent with theoretical predictions. Remarkably, these states are robust and self-guided even within the light cone continuum, functioning without ancillary cladding. This work paves the way for multi-dimensional manipulation of electromagnetic waves on 3D cladding-free photonic bandgap materials, enabling practical applications in 3D topological integrated photonic devices.